THE STARS SHINE DOWN - Sheldon, Sidney, author 498270 (London : Harper Collins Publisher, 1993)
Lara Cameron, a young and beautiful tycoon, has worked relentlessly for success, power and control of her career and personal relationships. She doesn't know that a discarded lover has vengeance in mind.